Neuroprotective Effects of Adenosine A1 Receptor Signaling on Cognitive Impairment Induced by Chronic Intermittent Hypoxia in Mice - Zhang, Yichun; Cao, Hongchao; Qiu, Xuehao; Xu, Danfen; Chen, Yifeng; Barnes, Gregory N.; Tu, Yunjia; Gyabaah, Adwoa Takyiwaa; Gharbal, Abdulla Husain Abdulla Ahmed; Peng, Chenlei; Cai, Jun; Cai, Xiaohong (Frontiers in Cellular Neuroscience, 2020)
Obstructive sleep apnea hypopnea syndrome (OSAHS) is a breathing disorder associated with cognitive impairment. However, the mechanisms leading to cognitive deficits in OSAHS remain uncertain. In this study, a mouse model of chronic intermittent hypoxia (CIH) exposures was applied for simulating the deoxygenation-reoxygenation events occurred in OSAHS. The conventional adenosine A1 receptor gene (A1R) knockout mice and A1R agonist CCPA- or antagonist DPCPX-administrated mice were utilized to determine the precise function of A1R signaling in the process of OSAHS-relevant cognitive impairment. We demonstrated that CIH induced morphological changes and apoptosis in hippocampal neurons. Further CIH blunted hippocampal long-term potentiation (LTP) and resulted in learning/memory impairment. Disruption of adenosine A1R exacerbated morphological, cellular, and functional damage induced by CIH. In contrast, activation of adenosine A1R signaling reduced morphological changes and apoptosis of hippocampal neurons, promoted LTP, and enhanced learning and memory. The modulation of A1R signaling may be mediated by the downstream Gα (i)-cAMP-PKC and syntaxin-relevant pathways. Taken together, A1R signaling plays a neuroprotective role in CIH-induced cognitive dysfunction and pathological changes in hippocampus.